2017
DOI: 10.1016/j.plantsci.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Loss of type-IV glandular trichomes is a heterochronic trait in tomato and can be reverted by promoting juvenility

Abstract: Glandular trichomes are structures with widespread distribution and deep ecological significance. In the Solanum genus, type-IV glandular trichomes provide resistance to insect pests. The occurrence of these structures is, however, poorly described and controversial in cultivated tomato (Solanum lycopersicum). Optical and scanning electron microscopy were used to screen a series of well-known commercial tomato cultivars, revealing the presence of type-IV trichomes on embryonic (cotyledons) and juvenile leaves.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 78 publications
4
60
0
1
Order By: Relevance
“…These differences were likely to have resulted from differences in the age of the plant as well as changes in environmental conditions between the glasshouse and the field. Trichome development is reported to change with the age of the plant (Telfer et al ., ; Vendemiatti et al ., ), with higher TD observed in the late leaves of tomato (Gurr and McGrath, ). Moreover, environmental factors, such as temperature, photoperiod, light intensity or soil humidity have direct effects on trichome development in several species, including tomato (Wellso and Hoxie, ; Gianfagna et al ., ; Chien and Sussex, ; Souza et al ., ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These differences were likely to have resulted from differences in the age of the plant as well as changes in environmental conditions between the glasshouse and the field. Trichome development is reported to change with the age of the plant (Telfer et al ., ; Vendemiatti et al ., ), with higher TD observed in the late leaves of tomato (Gurr and McGrath, ). Moreover, environmental factors, such as temperature, photoperiod, light intensity or soil humidity have direct effects on trichome development in several species, including tomato (Wellso and Hoxie, ; Gianfagna et al ., ; Chien and Sussex, ; Souza et al ., ).…”
Section: Discussionmentioning
confidence: 96%
“…These differences were likely to have resulted from differences in the age of the plant as well as changes in environmental conditions between the glasshouse and the field. Trichome development is reported to change with the age of the plant (Telfer et al, 1997;Vendemiatti et al, 2017), with higher TD observed in the late leaves of tomato (Gurr and McGrath, 2001).…”
Section: The Development Of Leaf Trichomes Is Influenced By Water Avamentioning
confidence: 99%
“…Furthermore, MT- Sst2 displayed an increased number of type-V non-glandular trichomes compared to both MT and LA1777 (Fig 5B). It was shown earlier that there appears to be a negative correlation between densities of glandular type-IV trichomes and the non-glandular type-V trichomes (Vendemiatti et al , 2017). The lower density of type-V trichomes in LA1777 could therefore be related to its high density of type-IV trichomes.…”
Section: Discussionmentioning
confidence: 92%
“…5B). This lack of type-IV trichomes in cultivated tomato has been linked to the transition from the juvenility to the adult phase (Vendemiatti et al , 2017). So, the region introgressed in MT- Sst2 is most likely not involved in heterochrony and/or type-IV trichome development, though we cannot discard the possibility that the region introgressed harbors genes controlling the density of type-V trichomes, as we cannot explain the increased type-V density in the introgression line compared to MT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation